A Study on Coverage Utilization and Quality of Maternal Care Services - Agarwal, Neeraj; Galhotra, Abhiruchi; Swami, H M (National Journal of Community Medicine, 2011)
The objectives of the study were to assess the utilization of various maternal services and to compare the quality of services provided by doctors and health workers in terms of components and advice received by pregnant women during antenatal period. It was a Cross-sectional Study conducted in a village on the border of Chandigarh (U.T.) and Mohali (Punjab). All the women who had delivered in the past three years in the village Palsora were included in the study. 92.4% of the pregnancies were registered, 53.2% of which received antenatal care by a Doctor and 46.8% by a health worker. The measuring of blood pressure was significantly higher by the doctor than the health workers who recorded weight more significantly. The advice provided by doctors was significantly higher than health workers regarding diet, danger signs, newborn care, family planning and natal care.